(untitled) (KASBIT Business Journal, 2012)
The purpose of this paper is profit analysis in Indian retailing with special reference to reliance retail value stores in Ranchi through sales analysis, footfall conversion analysis, average bill value and shrink & dump. In India retail industry is in its nascent stage. With new entrants into the market, the industry is going to rise and the competition is going to increase. Profit of any organization depends on the amount of sales. The sales can be increased by either increasing the footfalls i.e. attracting new customers, or, by increasing the footfall conversion rate i.e. making it best possible for each customer who enters the store to buy something and add to the sale. We all know that retaining a customer or persuading him/her to purchase is much more cost effective than to elicit a new one. Thus, a survey was conducted on 150 valued customers of three Reliance Retail Value Stores in Ranchi, to find out the reasons for the gap between footfall, and its conversion rate, so that the sales may be improved and thus the profitability at the least possible cost. The survey reveals various reasons for the gap such as lower assortment of products, absence of loose staples, poor service at billing counters etc., which if taken into account would definitely increase the footfall conversion rate and thus the profit. On the basis of the findings of this survey, if the concerned authority works upon to annihilate the loopholes, the sales will definitely be improved and profitability can be maintained at a reasonable height.